Penggunaan Model Joyful Learning Berbantuan Media Aplikasi Quizizz Terhadap Motivasi dan Hasil Belajar - Saputri, Eka Indah; Sutarjo, Ajo; Hanif, Muhammad (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Corona virus which has become a pandemic in Indonesia prompted the Minister of Education and Culture to issue a letter that the implementation of education during the COVID-19 emergency on March 24, 2020, was carried out online. Along with implementing the online learning policy at home mandated by the government, the role usually carried out by the education unit has now changed its function in the family unit. Because teaching activities are the core and implementation of learning, the quality of education and graduates are influenced by the teaching and learning process. Therefore, the researcher believes online teaching should get special attention, so students do not feel pressured and frustrated. Teachers can also learn according to their goals with syllabi and lesson plans. Learning that can provide new impetus in the learning process during a pandemic is fun learning, which is the choice, namely the joyful learning model. And so that this fun learning materializes for the learning process, a supportive media is needed, namely Quizizz. This study aims to analyze the motivation and learning outcomes of students who use the writing method of literature study or literature study by analyzing 20 journals, namely 14 national journals and 6 international journals. The analysis results in previous studies found that using the joyful learning model assisted by the Quizizz application potentially could increase students' motivation and learning outcomes during online learning during the covid-19 pandemic